Extreme dispersal or human-transport? The enigmatic case of an extralimital freshwater occurrence of a Southern elephant seal from Indiana - Ana M. Valenzuela-Toro; Maria H. Zicos; Nicholas D. Pyenson (PeerJ, 2020)
Elephant seals (Mirounga spp.) are the largest living pinnipeds, and the spatial scales of their ecology, with dives over 1 km in depth and foraging trips over 10,000 km long, are unrivalled by their near relatives. Here we report the discovery of an incomplete Holocene age Southern elephant seal (M. leonina) rostrum from Indiana, USA. The surviving material are two casts of the original specimen, which was collected in a construction excavation close to the Wabash River near Lafayette, Indiana. The original specimen was mostly destroyed for radiometric dating analyses in the 1970s, which resulted in an age of 1,260 ± 90 years before the present. The existence of sediments in the original specimen suggests some type of post depositional fluvial transportation. The prevalent evidence suggests that this male Southern elephant seal crossed the equator and the Gulf of Mexico, and then entered the Mississippi River system, stranding far upriver in Indiana or adjacent areas, similar to other reported examples of lost marine mammals in freshwater systems. Based on potential cut marks, we cannot exclude human-mediated transportation or scavenging by Indigenous peoples as a contributing factor of this occurrence. The material reported here represents by far the northernmost occurrence of a Southern elephant seal in the Northern Hemisphere ever recorded. The unusual occurrence of a top marine predator >1,000 km from the closest marine effluent as a potential extreme case of dispersal emphasizes how marine invasions of freshwater systems have happened frequently through historical (and likely geological) time.